THE EFFECTIVENESS OF THE INTERNAL CONTROL SYSTEM IN IMPROVING GOOD UNIVERSITY GOVERNANCE AT THE UNIVERSITY OF NORTH SUMATERA - Ariama Susanti; Deliana; Rahmat W. Sembiring (UPT Publikasi Ilmiah UNISBA, 2024)
The aim of this research is to determine the effectiveness of the Internal Control System in accordance with Government Regulation Number 60 of 2008 and the implementation of good governance according to the Directorate of Institutions and Cooperation of the Directorate General of Higher Education, Ministry of Education and Culture. Culture in 2014 and how the effectiveness of the internal control system realizes the implementation of good university governance at the University of North Sumatera. This research was conducted at the University of North Sumatera. Quantitative descriptive method with data collection techniques through distributing questionnaires and interviews with key informants used in this research with descriptive data analysis techniques. This research provides results regarding the effectiveness of the internal control system and the implementation of university governance in the effective or good category. The effectiveness of the internal control system provides support in implementing university governance. Keywords : Effectiveness of the internal control system, Good university governance, University governance.